2021
DOI: 10.1097/cco.0000000000000793
|View full text |Cite
|
Sign up to set email alerts
|

Current emerging MRI tools for radionecrosis and pseudoprogression diagnosis

Abstract: Purpose of review This review aims to cover current MRI techniques for assessing treatment response in brain tumors, with a focus on radio-induced lesions. Recent findings Pseudoprogression and radionecrosis are common radiological entities after brain tumor irradiation and are difficult to distinguish from real progression, with major consequences on daily patient care. To date, shortcomings of conventional MRI have been largely recognized but morphological sequences are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 157 publications
(195 reference statements)
0
14
0
Order By: Relevance
“…In the case of a suspected local relapse, MRI perfusion [ 8 ] and PET scan with F‑18-fluorethyltyrosin (FET) were used for non-invasive distinction between tumor relapse and radionecrosis. In case of persistent suspicion of local tumor regrowth, neurosurgical resection of the lesion was recommended to the patient.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of a suspected local relapse, MRI perfusion [ 8 ] and PET scan with F‑18-fluorethyltyrosin (FET) were used for non-invasive distinction between tumor relapse and radionecrosis. In case of persistent suspicion of local tumor regrowth, neurosurgical resection of the lesion was recommended to the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor water ADC has been reported to be lower in true disease progression as compared to pseudoprogression, however meta-analyses have shown that while diagnostic performance was superior to that of conventional anatomical imaging it was poorer when compared to MRI measurements of perfusion (13). Dynamic (32,(35)(36)(37)(38). However, while meta-analysis has shown that 1 H MRS is superior to anatomical MRI, DWI-MRI and MRI-based perfusion measurements in distinguishing true progression from pseudoprogression (39) the low signal-to-noise ratio in spectroscopy means that scan times are long.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic modalities may help to differentiate between PRN and tumor progression. That includes MRI spectroscopy, positron emission tomography, single-photon emission computed tomography, and high-resolution MRI with the assessment of perfusion and diffusion [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, the only 100% reliable method of confirmation of progressive BCBM after SRS/FSRT is a pathological examination of the resected tumor.…”
Section: Diagnosis Of Intracranial Progressionmentioning
confidence: 99%